Genetic Polymorphisms in Serotonin Transporter (5HTT) and Catechol-O-Methyltransferase (COMT) On Dental Implant Loss - Pilot Project - Thais Mariana Neves CHAVES; Paula Cruz Porto SPADA; Michelle Nascimento EGER; Marilisa Carneiro Leão GABARDO; João César ZIELAK; Tatiana Miranda DELIBERADOR; João Armando BRANCHER (Tehran University of Medical Sciences, 2021)
No Abstract